Pooling of Immunomagnetic Separation Beads Does Not Affect Detection Sensitivity of Six Major Serogroups of Shiga Toxin–Producing Escherichia coli in Cattle Feces - Noll, Lance W.; Baumgartner, William C.; Shridhar, Pragathi B.; Cull, Charley A.; Dewsbury, Diana M.; Shi, Xiaorong; Cernicchiaro, Natalia; Renter, David G.; Nagaraja, T.G. (Journal of food protection, 2016)
Shiga toxin-producing Escherichia coli (STEC) of the serogroups O26, O45, O103, O111, O121, and O145, often called non-O157 STEC, are foodborne pathogens. Cattle are asymptomatic reservoirs for STEC; the organisms reside in the hindgut and are shed in the feces, which serve as the source of food product contaminations. Culture-based detection of non-O157 STEC involves an immunomagnetic separation (IMS) step to capture the specific serogroups in complex matrices, such as feces. The IMS procedure is time consuming and labor intensive because of the need to subject each fecal sample to six individual beads. Therefore, our objective was to evaluate whether pooling of IMS beads affects sensitivity of non-O157 STEC detection compared with using individual IMS beads. The evaluation was done by comparing detection of serogroups in feces spiked with pure cultures (experiments 1 and 2) and from feces (n = 384) of naturally shedding cattle (experiment 3). In spiked fecal samples, detection with pools of three, four, six, or seven beads was similar to, or at times higher than, detection with individual IMS beads. In experiment 3, the proportions of fecal samples that tested positive for the six serogroups as detected by individual or pooled beads were similar. Based on noninferiority tests, detection with pooled beads was not substantially inferior to detection with individual beads (P > 0.05). In conclusion, the pooling of IMS beads is a better option for detection of STEC serogroups in fecal samples compared with individual beads because the procedure saves time and labor and has the prospect of a higher throughput.